The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1104/pp.010791
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Enhances Water Transport in Hypoxic Aspen

Abstract: Water transport was examined in solution culture grown seedlings of aspen (Populus tremuloides) after short-term exposures of roots to exogenous ethylene. Ethylene significantly increased stomatal conductance, root hydraulic conductivity (L p ), and root oxygen uptake in hypoxic seedlings. Aerated roots that were exposed to ethylene also showed enhanced L p . An ethylene action inhibitor, silver thiosulphate, significantly reversed the enhancement of L p by ethylene. A short-term exposure of excised roots to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 49 publications
(28 reference statements)
2
48
1
Order By: Relevance
“…Root respiration was measured 2, 8, 16 and 27 days after flooding treatment was imposed. Root systems of black spruce and tamarack seedlings (n=5 per species treatment combination) were placed in an airtight cylinder containing half-strength Hoagland's solution (Kamaluddin and Zwiazek 2002). Oxygen uptake rates were recorded every 2 min for 20 min.…”
Section: Root Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Root respiration was measured 2, 8, 16 and 27 days after flooding treatment was imposed. Root systems of black spruce and tamarack seedlings (n=5 per species treatment combination) were placed in an airtight cylinder containing half-strength Hoagland's solution (Kamaluddin and Zwiazek 2002). Oxygen uptake rates were recorded every 2 min for 20 min.…”
Section: Root Respirationmentioning
confidence: 99%
“…Root respiration has been shown to decline as a result of hypoxia in wheat (Huang and Johnson 1995), and aspen (Kamaluddin and Zwiazek 2002). Carbohydrate concentrations may remain the same or increase in roots and shoots under hypoxic conditions (Huang 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin inhibits the endocytosis of PIP2 in Arabidopsis (Paciorek et al, 2005), while exogenous auxin has been found to inhibit root and cell hydraulic conductivity in Arabidopsis (Péret et al, 2012). Ethylene can enhance (Kamaluddin and Zwiazek, 2002) or inhibit (Li et al, 2009) L pr . In the case of the latter, inhibition caused by phosphorus deficiency appears to be mediated by ethylene.…”
Section: Shoot-to-root Signaling In Aquaporin Regulationmentioning
confidence: 99%
“…A general inhibitor of AQP activities, HgCl 2 , decreased ethylene-enhanced water flow in aspen (Populus spp.) roots (Kamaluddin and Zwiazek, 2002). A protein kinase inhibitor, okadaic acid, could inhibit the ethylene-induced phosphorylation in mung bean (Vigna radiata) hypocotyls (Kim et al, 1997), orchid petals (Wang et al, 2001), and pea (Berry et al, 1996;Kwak and Lee, 1997), and the inhibitor also inhibited the phosphorylation of AQP PM28A in spinach leaves (Johansson et al, 1996).…”
Section: Ethylene Regulates Rh-pip2;1 Expression In Rose Petalsmentioning
confidence: 99%